PENERAPAN MODEL PEMBELAJARAN BACK TO BACK TECHNIQUE UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IX SMP NEGERI 20 MAKASSAR - Videlis Jeranu; Sitti Marlina (EDUCATIONAL JOURNAL : General and Specific Research, 2021)
This study aims to improve students' social studies learning outcomes through the application of the Back To Back Technique learning model. The subjects of this study were class IX students of SMP Negeri 20 Makassar in the 2020/2021 academic year with a total of 20 students. This research is a classroom action research which consists of 2 cycles and each cycle consists of 4 meetings. The data obtained were analyzed descriptively. The results showed that the application of the Back To Back Technique learning model could improve student learning outcomes. The increase in learning outcomes is shown by the results of research from cycle I to cycle II, namely the average value of student learning outcomes increases from 70 to 80. The results of this study can be concluded that the application of the Back To Back Technique learning model can improve class student learning outcomes. IX SMP Negeri 20 Makassar.